SHADOW PUPPET ARTS AS THE FORMATION OF YOUNG GENERATION CHARACTER - Yogi Laksito Pramono; Suyanto Suyanto; Adam Wahida (Universitas Sebelas Maret, 2017)
The Indonesian nation has a variety of arts and culture’s that flourishes in the community. High variety of art and culture’s that developed in the community describes the richness of art and culture in Indonesia. The variety of cultural arts include indigenous Indonesian culture scattered in areas throughout Indonesia, such as shadow puppet culture.Shadow puppet is a show organized by Javanese community and had been going on for hundreds of years, therefore it was already a Javanese tradition or culture. Shadow puppet for Javanese society is a cultural heritage that has its own characteristics and enormous charm.Shadow puppet is fully of noble values contained in it, which can be a life guidance for Javanese society. Shadow puppet is an adipeni and adiluhung art, it means that shadow puppet is not only a beautiful or aesthetic spectacle, but also as a guidance which it is contained ethics or moral virtue of life. The shadow puppet artists must have an idea to give and pass on the science of shadow puppet art to anybody so that the science of shadow puppet art is not faded and dim by the development of this modern age. From the literature results, we can indicate that by studying the shadow puppet from the character's point of view, it will cultivate good qualities for the younger generation.